2010
DOI: 10.1111/j.1365-2249.2010.04214.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific antibodies to soluble alpha-synuclein conformations in intravenous immunoglobulin preparations

Abstract: SummaryAlpha-synuclein is the major protein in Lewy bodies, the hallmark pathological finding in Parkinson's disease (PD) and dementia with Lewy bodies (DLB). Although normally intracellular, it also can be secreted, so extracellular alpha-synuclein may contribute to neuronal injury. Serum antibodies to alpha-synuclein could exert protective effects by increasing alpha-synuclein's movement out of the brain and, if they cross the blood-brain barrier, by inhibiting its neurotoxic effects. The objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
3
17
0
1
Order By: Relevance
“…Western blot analysis showed an increase in monomeric a-synuclein at 10 and 40 mM treatment of 6-OHDA but appearance of distinct oligomeric bands of a-synuclein was noticed from 75 mM concentration of 6-OHDA. This is in alignment with earlier studies, where an increase in oligomeric bands of a-synuclein has been noticed under oxidative stress [Cappai et al, 2005;Hunya et al, 2008;Patrias et al, 2010;Lee and Kamitani, 2011]. Since phosphorylation of a-synuclein at serine 129 has been related to PD (based on data from post mortem studies) [Fujiwara et al, 2002;Anderson et al, 2006], we looked into the expression of pSyn-129 in SH-SY5Y cells under 6-OHDA toxicity.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Western blot analysis showed an increase in monomeric a-synuclein at 10 and 40 mM treatment of 6-OHDA but appearance of distinct oligomeric bands of a-synuclein was noticed from 75 mM concentration of 6-OHDA. This is in alignment with earlier studies, where an increase in oligomeric bands of a-synuclein has been noticed under oxidative stress [Cappai et al, 2005;Hunya et al, 2008;Patrias et al, 2010;Lee and Kamitani, 2011]. Since phosphorylation of a-synuclein at serine 129 has been related to PD (based on data from post mortem studies) [Fujiwara et al, 2002;Anderson et al, 2006], we looked into the expression of pSyn-129 in SH-SY5Y cells under 6-OHDA toxicity.…”
Section: Discussionsupporting
confidence: 52%
“…Densitometric analysis represented in Figure 4D, indeed showed a significant increase in the 19 kDa a-synuclein band at the 10 and 40 mM 6-OHDA treatment (P < 0.05) in comparison to control. As depicted in Figure 4C, the Western blot analysis of cells, treated with higher concentrations (75, 100, and 150 mM) of 6-OHDA showed an additional band at $24 kDa for a-synuclein which refers to a covalently modified isoform of the protein [Cappai et al, 2005;Hunya et al, 2008;Patrias et al, 2010;Lee and Kamitani, 2011]. Densitometric analysis for the 19 kDa (Fig.…”
Section: Mitochondrial Membrane Potential Of Sh-sy5y Cells Under 6-ohmentioning
confidence: 95%
“…IVIG administration to patients with DLB and MSA has also been reported [39,40] but little is known of its effects on α-synuclein. In our previous study [34], as shown by western blots of reducing/denaturing gels, IVIG preparations did not prevent short-term (four-day) development of α-synuclein soluble oligomers, although alterations were seen in the distribution of the oligomer bands. The objectives of the present study were to further examine the effects of IVIG on α-synuclein aggregation, by determining its effects on the formation of longer-term (nine-day) α-synuclein soluble oligomers and amorphous aggregates as well as preformed α-synuclein oligomers, and to determine its possible protective effects against α-synuclein oligomer neurotoxicity.…”
Section: Introductionmentioning
confidence: 91%
“…The objectives of the present study were to further examine the effects of IVIG on α-synuclein aggregation, by determining its effects on the formation of longer-term (nine-day) α-synuclein soluble oligomers and amorphous aggregates as well as preformed α-synuclein oligomers, and to determine its possible protective effects against α-synuclein oligomer neurotoxicity. The IVIG preparation Gammagard (Baxter Healthcare) was chosen for this study because in our earlier investigation [34] it appeared to contain the highest specific antibody levels to α-synuclein monomer among three IVIG preparations examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation